Long‐term associations of cigarette smoking in early mid‐life with predicted brain aging from mid‐ to late life. (28th October 2021) - Whitsel, Nathan; Reynolds, Chandra A.; Buchholz, Erik J.; Pahlen, Shandell; Pearce, Rahul C.; Hatton, Sean N.; Elman, Jeremy A.; Gillespie, Nathan A.; Gustavson, Daniel E.; Puckett, Olivia K.; Dale, Anders M.; Eyler, Lisa T.; et al.
Abstract: Background and aims: Smoking is associated with increased risk for brain aging/atrophy and dementia. Few studies have examined early associations with brain aging. This study aimed to measure whether adult men with a history of heavier smoking in early mid‐life would have older than predicted brain age 16–28 years later. Design: Prospective cohort observational study, utilizing smoking pack years data from average age 40 (early mid‐life) predicting predicted brain age difference scores (PBAD) at average ages 56, 62 (later mid‐life) and 68 years (early old age). Early mid‐life alcohol use was also evaluated. Setting: Population‐based United States sample. Participants/cases: Participants were male twins of predominantly European ancestry who served in the United States military between 1965 and 1975. Structural magnetic resonance imaging (MRI) began at average age 56. Subsequent study waves included most baseline participants; attrition replacement subjects were added at later waves. Measurements: Self‐reported smoking information was used to calculate pack years smoked at ages 40, 56, 62, and 68. MRIs were processed with the Brain‐Age Regression Analysis and Computation Utility software (BARACUS) program to create PBAD scores (chronological age—predicted brain age) acquired at average ages 56 ( n  = 493; 2002–08), 62 ( n  = 408; 2009–14) and 68 ( n  = 499; 2016–19). Findings: In structural equation modeling, age 40 pack years predicted more advanced age 56 PBAD [β = −0.144, P  = 0.012, 95% confidence interval (CI) = –0.257, −0.032]. Age 40 pack years did not additionally predict PBAD at later ages. Age 40 alcohol consumption, but not a smoking × alcohol interaction, predicted more advanced PBAD at age 56 (β = −0.166, P  = 0.001, 95% CI = –0.261, –0.070) with additional influences at age 62 (β = −0.115, P  = 0.005, 95% CI = –0.195, –0.036). Age 40 alcohol did not predict age 68 PBAD. Within‐twin‐pair analyses suggested some genetic mechanism partially underlying effects of alcohol, but not smoking, on PBAD. Conclusions: Heavier smoking and alcohol consumption by age 40 appears to predict advanced brain aging by age 56 in men.